STUDY OF SERUM URIC ACID LEVELS IN PATIENTS DIAGNOSED WITH METABOLIC SYNDROME IN A HOSPITAL-BASED STUDY IN WEST BENGAL - GUNJAN KUMAR MANDAL (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The occurrence of hyperuricemia is growing even in developing countries. It has been known to be associated with metabolic syndrome (MetS). MetS is a bunch of numerous metabolic disorders including reduced high-density lipoprotein cholesterol (HDL-C), hypertension, hyperglycemia, abdominal obesity, and raised triglyceride level in serum. Methods: The present work was done in the Department of Biochemistry in combination with Medicine Department, SRIMS and Sanaka Hospital, Durgapur, WB, India. A total of 50 diagnosed MetS patients were selected for further studies and same number (50) of healthy volunteers controls without MetS were selected. Diagnosis of MetS was done according to the National Cholesterol Education Program Adult Treatment Panel-III. Results: In our study, the level of serum uric acid (SUA) is high in MetS patients (7.8 mg/dL) compared to control group (4.6 mg/dL). The compared between two groups was statistically significant (p<0.000). Conclusion: Our study showed that the components of MetS are increased with rise in the concentrations of SUA.